2007
DOI: 10.1177/1082013207082463
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Extrudates Prepared with Blends of Wheat Flour/Pinto Bean Meal with Added Wheat Bran

Abstract: Blends made of wheat flour and bean meal at various levels of moisture and bran content, were subjected to extrusion cooking by varying temperature and screw speed. Extrudates were analysed for expansion index, bulk density, apparent viscosity, water absorption index and water solubility index using a secondorder rotatable central composite design. Excepting water absorption index, functional properties were significantly affected ( p50.05) by levels of moisture, bran or extrusion conditions. Expansion index d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 22 publications
10
45
0
6
Order By: Relevance
“…Therefore, the decreasing trend of WSI with feed moisture content is expected and in agreement with previous reports [23,42].…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)supporting
confidence: 93%
“…Therefore, the decreasing trend of WSI with feed moisture content is expected and in agreement with previous reports [23,42].…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)supporting
confidence: 93%
“…This could be as a result of the disruption of covalent or non-covalent bonds in the carbohydrate and protein moieties, leading to smaller, more soluble molecular fragments [45,46]. These observations confirm similar findings reported for starch-based extrudates obtained either using single or twin screw extrusion [47,48]. Dextrinization is well known as the predominant mechanism of starch degradation during low moisture extrusion [37].…”
Section: Water Solubility Index Y Wsisupporting
confidence: 85%
“…It has been reported that when starch depolymerization increased and the length of amylose and amylopectin chains shortened, the WSI increased (Balandran-Quintana et al, 1998). Similarly, Hernandez-Diaz and coworkers observed that the lower WSI was related with lower starch degradation (Hernandez-Diaz et al, 2007). Another report showed that gelatinizing higher WSI products would need less energy (Kaur & Singh, 2006).…”
Section: Water Holding Capacity (Whc) and Water Soluble Index (Wsi)mentioning
confidence: 96%